Effects of carbon additives on the properties of ZrB2–based composites: A review. Issue 7 (May 2018) - Asl, Mehdi Shahedi; Nayebi, Behzad; Ahmadi, Zohre; Zamharir, Mehran Jaberi; Shokouhimehr, Mohammadreza
Abstract: This review presents the recent achievements on carbon additives incorporated in ZrB2 ceramics, improved properties, and their advancements. Monolithic ZrB2 ceramics have broad potential applications, but their critical drawbacks such as poor damage tolerance, and weak oxidation and ablation resistance confines their applicability. It is an important issue to resolve these shortages in physiochemical properties by engineering the composite ingredients and process design of the ceramic counterparts for an extensive production and applications, which are especially essential in high–tech industries and products. Carbon additives have exceptional characteristics including low density, low cost, and excellent thermo–mechanical stability. These materials have been incorporated in ZrB2 ceramics to enhance their efficiency and form practical composite ceramics. Although addition of the secondary carbonaceous phases is generally supposed to improve the mechanical properties of ZrB2 composites, it may also result in a decrease in other aspects of performance, comparing with monolithic ZrB2 ceramics. In this work, we reviewed the methods and strategies for the preparation of carbon modulated ZrB2 ceramic composites. Moreover, the advantages, disadvantages, and the productivity of the introduced composite ceramics have been explored and featured.